Mitochondrial toxicants in Xian-Ling-Gu-Bao induce liver injury by regulating the PI3K/mTOR signaling pathway: an in vitro study - Shujuan Piao; Hongwei Lin; Xia Tao; Wansheng Chen (BMC, 2022)
Abstract Background Drug-induced mitochondrial toxicity is thought to be a common mechanism of drug hepatotoxicity. Xian-Ling-Gu-Bao (XLGB) oral preparation is a commonly used drug for osteoporosis in China. Classical safety evaluation studies have shown that the entire preparation and six Chinese herbal medicines have high safety, but the incidence of drug-induced liver damage due to XLGB remains high, the mechanism and toxic substances causing liver injury are still unclear. The purpose of this study is to identify compounds with potential mitochondrial liabilities in XLGB, and to clarify their underlying mechanisms and related pathways. Methods The mitochondrial function analysis was performed using an extracellular flux assay, which simultaneously monitored both oxygen consumption rate (OCR) and extracellular acidification rate (ECAR). Through network pharmacology and in vitro experimental verification, the potential protein targets, signaling pathways and molecular mechanism of mitochondrial toxicity have been studied. Results We observed a significant decrease in mitochondrial respiration of Psoraleae Fructus and its five compounds in fundamental bioenergetics parameters such as basal respiration, ATP-linked production and maximal respiration, indicating mitochondrial dysfunction. The network pharmacology results showed that the influence of XLGB on mitochondrial dysfunction was closely related to PI3K-Akt signaling pathway, mTOR signaling pathway and Apoptosis. Western blot showed that the levels of mTOR, p-mTOR (Ser2448), Raptor, PI3K (p110α), Beclin 1, ATG5 and Caspase-9 were up-regulated after treatment with psoralidin, psoralen and bavachin, and the expression of Bcl-2 was down-regulated after bavachinin treatment. Conclusions The hepatotoxicity of XLGB is associated with mitochondrial dysfunction. Five compounds in Psoraleae Fructus showed mitochondrial damage, they are psoralidin, isobavachalcone, bavachinin, bavachin and psoralen, especially psoralidin showed significant reduction in reserve capacity and respiratory control ratios. The molecular mechanism is related to the activation of PI3K/mTOR signaling pathway to inhibit autophagy and induce mitochondrial apoptosis.